2021
DOI: 10.1210/clinem/dgab391
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 2 mRNA-Binding Protein 2—a Potential Link Between Type 2 Diabetes Mellitus and Cancer

Abstract: Context Type 2 diabetes mellitus (T2DM) and cancer share a variety of risk factors and pathophysiological features. It is becoming increasingly accepted that the two diseases are related, and that T2DM increases the risk of certain malignancies. This review summarizes recent advancements in the elucidation of functions of insulin-like growth factor 2 (IGF-2) mRNA-binding protein 2 (IGF2BP2) in T2DM and cancer. Evidence Acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 127 publications
2
22
0
Order By: Relevance
“…3 Type 2 DM is associated with greater risk for a variety of cancers, but there are conflicting data regarding the influence of T2DM, on DTC. [23][24][25] We found the highest number of malignant TN in patients with DM and elevated A1c (≥7%, 7/25 = 30.4%; p = 0.046), supporting an association between DTC and DM. However, given the small size of our cohort, this observation needs to be verified by larger, independent studies.…”
Section: Discussionsupporting
confidence: 57%
“…3 Type 2 DM is associated with greater risk for a variety of cancers, but there are conflicting data regarding the influence of T2DM, on DTC. [23][24][25] We found the highest number of malignant TN in patients with DM and elevated A1c (≥7%, 7/25 = 30.4%; p = 0.046), supporting an association between DTC and DM. However, given the small size of our cohort, this observation needs to be verified by larger, independent studies.…”
Section: Discussionsupporting
confidence: 57%
“…In other cancers, IGF2BP2 has been reported to regulate numerous tumorigenesis [ 16–18 ]. For example, in hepatocellular carcinoma, researchers found that IGF2BP2 targets thousands of mRNA transcripts, which may be involved in the progression.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical trial suggested that the wild C allele of IGF2BP2 had a protective effect against T2DM in obese subjects of Chinese Han population [ 158 ]. IGF2BP2 can inhibit the expression of UCP1 by binding to UCP1 mRNA, thereby enhancing insulin resistant [ 159 , 160 ]. Furthermore, mTOR phosphorylates IGF2BP2 and facilitates its binding to IGF-2 mRNA, thus enhancing IGF-2 expression [ 160 , 161 ].…”
Section: Rna-rbps Interaction In Diabetes and Its Complicationsmentioning
confidence: 99%
“…IGF2BP2 can inhibit the expression of UCP1 by binding to UCP1 mRNA, thereby enhancing insulin resistant [ 159 , 160 ]. Furthermore, mTOR phosphorylates IGF2BP2 and facilitates its binding to IGF-2 mRNA, thus enhancing IGF-2 expression [ 160 , 161 ].…”
Section: Rna-rbps Interaction In Diabetes and Its Complicationsmentioning
confidence: 99%